Effects of flexible sacrum positions during the second stage of labour on maternal and neonatal outcomes: A systematic review and meta‐analysis. Issue 17 (25th June 2020) - Zang, Yu; Lu, Hong; Zhao, Yang; Huang, Jing; Ren, Lihua; Li, Xia
Abstract: Aims and objectives: To assess the effects of flexible sacrum positions on mode of delivery, duration of the second stage of labour, perineal trauma, postpartum haemorrhage, maternal pain, abnormal foetal heart rate patterns and Apgar scores based on published literature. Background: Maternal positions served as a nonmedical intervention may facilitate optimal maternal and neonatal outcomes during labour. Flexible sacrum positions are conducive to expanding pelvic outlet. Whether flexible sacrum positions have positive effects on maternal and neonatal well‐being is a controversial issue under heated discussion. Design: We performed a systematic review and meta‐analysis based on PRISMA guidelines. Methods: Randomised controlled trials (RCTs) comparing any flexible sacrum position with non‐flexible sacrum position in the second stage of labour were included. PubMed, EMBASE, Cochrane Library, CINAHL, CNKI (China National Knowledge Infrastructure), SinoMed and Wanfang databases were searched from inception to 11 March 2019 for published RCTs. Risk of bias was assessed by the Cochrane criteria, and random‐effects meta‐analyses were conducted by RevMan 5.3. Results: Sixteen studies (3, 397 women) published in English were included. Flexible sacrum positions in the second stage of labour could reduce the incidence of operative delivery, instrumental vaginal delivery, caesarean section, episiotomy, severe perineal trauma, severe pain and shorten the duration of active pushing phase in the second stage of labour. However, flexible sacrum positions may increase the incidence of mild perineal trauma. There was no significant difference in the duration of the second stage of labour, maternal satisfaction and other outcomes. Conclusions: Flexible sacrum positions are superior in promoting maternal well‐being during childbirth. However, several results require careful interpretation. More rigorous original studies are needed to further explore their effects. Relevance to clinical practice: The results support the use of flexible sacrum positions. Flexible sacrum positions are recommended to apply flexibly or tailor to individual woman's labour progress.